If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 5a = 3(6a + -9) Reorder the terms: 12 + 5a = 3(-9 + 6a) 12 + 5a = (-9 * 3 + 6a * 3) 12 + 5a = (-27 + 18a) Solving 12 + 5a = -27 + 18a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-18a' to each side of the equation. 12 + 5a + -18a = -27 + 18a + -18a Combine like terms: 5a + -18a = -13a 12 + -13a = -27 + 18a + -18a Combine like terms: 18a + -18a = 0 12 + -13a = -27 + 0 12 + -13a = -27 Add '-12' to each side of the equation. 12 + -12 + -13a = -27 + -12 Combine like terms: 12 + -12 = 0 0 + -13a = -27 + -12 -13a = -27 + -12 Combine like terms: -27 + -12 = -39 -13a = -39 Divide each side by '-13'. a = 3 Simplifying a = 3
| 11x-132=5x-6 | | (2x/e^x)=0 | | 5x+y-8=0 | | 40/9-Z=8 | | (2x+1)=39 | | 77-x=0 | | 3x^3-40x^2+97x+10=0 | | 65=2x+3x-10 | | 6n=1+4n+19 | | 2sec^2x=3-tanx | | 3-21y-24y^2=0 | | X/2=2x-1/3 | | 30x/5+15x/3=15 | | -r^3t-rt^3=0 | | 3x^2-6y=0 | | 5=7x+3 | | 5x+30=20 | | 14x^2+33x+10=0 | | 24=18/x | | 14b-10= | | -5x+40=6x-60 | | 2(10)=24-2(10) | | -4=4v | | 88=x+x-6 | | -x=-77 | | X+2x-5=0 | | 10=24-2(10) | | 3f=-3+12 | | x+x-6=88 | | 400=0.14+2 | | x-6+x=88 | | 6x/3+7/15x+3 |